Polarizing plate and polarizing plate coil
By using an organic solvent solution of thermoplastic acrylic resin on the polarizing plate to form the first protective layer with a high glass transition temperature and the second protective layer of the resin film, the problem of reducing optical characteristics of the polarizing plate in a heating and humidification environment is solved, and the problem of reducing optical characteristics of the polarizing plate in a heating and humidified environment is achieved. Improved durability and performance.
Patent Information
- Application Number
- CN202411474322.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2018-12-27
- Filing Date
- 2019-12-26
- Publication Date
- 2024-12-31
AI Technical Summary
The existing polarizers have reduced optical characteristics and insufficient durability in heating and humidified environments, especially very thin polarizers have shown significant performance degradation in such environments.
The organic solvent solution of thermoplastic acrylic resin is used as the material for the first protective layer, and the film is formed by curing, and the glass transition temperature is set to 95°C or above. The resin film is used as the second protective layer to ensure the polarizing plate Overall thickness and optical properties.
Even in a heating and humidification environment, the optical characteristics and durability of the polarizer are significantly improved, and the variations in the transmission and polarization of the monomer are less than the predetermined value, ensuring the efficient performance of the polarizer.
Smart Images

Figure CN119224890A_ABST
Abstract
Description
[0001] This application is a divisional application of an application filed on December 26, 2019, with application number 201980086299.8 and invention name “Polarizing Plate and Polarizing Plate Coil”. Technical Field
[0002] The invention relates to a polarizing plate and a polarizing plate roll. Background Art
[0003] In image display devices (such as liquid crystal display devices and organic EL display devices), a polarizing plate is often arranged on at least one side of the display unit due to the image forming method. In recent years, image display devices have been further thinned and flexible, and with this, there is a strong demand for thinning of polarizing plates. However, the thinner the polarizing plate, the more obvious the durability problem of reduced optical properties in a heated and humidified environment.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-210474 Summary of the invention
[0007] Problem that the invention aims to solve
[0008] The present invention has been made to solve the above-mentioned conventional problems, and a main object of the present invention is to provide a polarizing plate that is excellent in durability even though it is very thin.
[0009] Solutions for solving problems
[0010] The polarizing plate of the present invention comprises a polarizer, a first protective layer disposed on one side of the polarizer, and a second protective layer disposed on the other side of the polarizer. The first protective layer is composed of a solidified product of a coating film of an organic solvent solution of a thermoplastic acrylic resin, and the glass transition temperature of the first protective layer is above 95° C. The second protective layer is composed of a resin film.
[0011] In one embodiment, the thickness of the first protective layer is 10 μm or less.
[0012] In one embodiment, the iodine adsorption amount of the first protective layer is 4.0 wt % or less.
[0013] In one embodiment, the thermoplastic acrylic resin has at least one selected from the group consisting of a lactone ring unit, a glutaric anhydride unit, a glutarimide unit, a maleic anhydride unit, and a maleimide unit.
[0014] In one embodiment, the first protective layer has an in-plane retardation Re(550) of 0 nm to 10 nm, and a thickness direction retardation Rth(550) of -20 nm to +10 nm.
[0015] In one embodiment, the first protective layer is disposed on a display unit side of the image display device, and the second protective layer is disposed on an opposite side of the display unit. In one embodiment, the polarizing plate is disposed on a viewing side of the image display device.
[0016] According to another aspect of the present invention, a polarizing plate roll is provided. The polarizing plate roll is obtained by winding the polarizing plate into a roll.
[0017] Effects of the Invention
[0018] According to the present invention, by forming one of the protective layers disposed on both sides of the polarizer from a cured product of a coating film of an organic solvent solution of a thermoplastic acrylic resin and setting its glass transition temperature to a predetermined value or higher, a polarizing plate having excellent durability even if very thin can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a schematic cross-sectional view of a polarizing plate according to one embodiment of the present invention.
[0020] Figure 2 This is a schematic diagram showing an example of a drying shrinkage treatment using a heating roller in a method for producing a polarizing plate according to an embodiment of the present invention. DETAILED DESCRIPTION
[0021] A. Overview of Polarizing Plate
[0022] Figure 1 : is a schematic cross-sectional view of a polarizing plate according to an embodiment of the present invention. The polarizing plate 100 shown in the figure has a polarizer 10, a first protective layer 20 disposed on one side of the polarizer 10, and a second protective layer 30 disposed on the other side of the polarizer 10. The thickness of the polarizer 10 is preferably less than 8 μm. When the polarizing plate 100 is applied to an image display device, it can be disposed on the visual recognition side of the display unit or on the side opposite to the visual recognition side (back side). In any case, the first protective layer 20 can be disposed on the display unit side or on the side opposite to the display unit (outside). In one embodiment, the polarizing plate 100 is disposed on the visual recognition side of the display unit (resulting in an image display device), and the first protective layer 20 is disposed on the display unit side. By configuring the first protective layer 20 on the display unit side, a polarizing plate having both excellent optical properties and excellent durability can be achieved.
[0023] The polarizing plate may be in the form of a long strip or a single sheet. When the polarizing plate is in the form of a long strip, it is preferably wound into a roll to form a polarizing plate roll.
[0024] Typically, the polarizing plate has an adhesive layer as the outermost layer on one side (typically, the display unit side) and can be attached to the display unit. If necessary, a surface protection film and / or a carrier film can be temporarily bonded to the polarizing plate in a removable manner to strengthen and / or support the polarizing plate. When the polarizing plate includes an adhesive layer, a separator is temporarily bonded to the surface of the adhesive layer in a removable state, so that the adhesive layer can be protected until the actual use and the polarizing plate can be rolled up.
[0025] In an embodiment of the present invention, the first protective layer 20 is composed of a cured product of a coating film of an organic solvent solution of a thermoplastic acrylic resin. With such a composition, the protective layer can be made very thin (for example, less than 10 μm). Furthermore, the protective layer can be formed directly on the polarizer (that is, without an adhesive layer or an adhesive layer). According to an embodiment of the present invention, as described above, the polarizer and the first protective layer are very thin, and the adhesive layer or the adhesive layer can be omitted, so the total thickness of the polarizing plate can be made very thin. The second protective layer is composed of a resin film. By forming the second protective layer from a resin film, the handleability of the polarizing plate (for example, roller transportability) can be ensured.
[0026] The total thickness of the polarizing plate is, for example, 50 μm or less, preferably 45 μm or less, more preferably 40 μm or less, and further preferably 35 μm or less. The lower limit of the total thickness of the polarizing plate may be, for example, 25 μm.
[0027] Furthermore, in an embodiment of the present invention, the glass transition temperature (Tg) of the first protective layer 20 is 95°C or more, preferably 100°C or more, more preferably 105°C or more, further preferably 110°C or more, and particularly preferably 115°C or more. When the Tg of the first protective layer is within such a range, a polarizing plate that is very thin and has excellent durability can be realized by utilizing the synergistic effect of the effect brought about by the protective layers being arranged on both sides of the polarizer and the first protective layer being composed of a cured product of a coating film of an organic solvent solution of a thermoplastic acrylic resin. Specifically, a polarizing plate in which the reduction of optical properties is suppressed even in a heated and humidified environment can be realized. On the other hand, the Tg of the first protective layer is preferably below 300°C, more preferably below 250°C, further preferably below 200°C, and particularly preferably below 160°C. When the Tg of the first protective layer is within such a range, excellent formability can be achieved.
[0028] As described above, according to an embodiment of the present invention, a polarizing plate in which the reduction of optical characteristics is suppressed even in a heated and humidified environment can be realized. The change ΔTs of the single transmittance Ts and the change ΔP of the polarization degree P of such a polarizing plate after being placed in an environment of 85°C and 85% RH for 48 hours are very small. The single transmittance Ts can be measured using, for example, an ultraviolet-visible spectrophotometer (manufactured by JASCO Corporation, product name "V7100"). The polarization degree P is calculated using the following formula from the single transmittance (Ts), parallel transmittance (Tp) and orthogonal transmittance (Tc) measured using an ultraviolet-visible spectrophotometer.
[0029] Polarization degree (P) (%) = {(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100
[0030] It should be noted that the above Ts, Tp and Tc are Y values obtained by measuring using a 2 degree field of view (C light source) of JIS Z 8701 and performing a sensitivity correction. In addition, Ts and P are substantially characteristics of the polarizer. ΔTs and ΔP are respectively obtained by the following formulas.
[0031] ΔTs(%)=Ts 48 -Ts0
[0032] ΔP(%)=P 48 -P0
[0033] Here, Ts0 is the initial single transmittance before placement, and Ts 48 is the transmittance of the monomer after placement, P0 is the polarization degree before placement (initial), P 48 is the degree of polarization after standing. ΔTs is preferably 3.0% or less, more preferably 2.7% or less, and even more preferably 2.4% or less. ΔP is preferably -0.05% to 0%, more preferably -0.03% to 0%, and even more preferably -0.01% to 0%.
[0034] As described above, the polarizing plate of the present invention is very thin, and therefore, it can be suitably used in a flexible image display device. More preferably, the image display device has a curved shape (substantially a curved display screen), and / or can be bent or folded. As specific examples of image display devices, liquid crystal display devices, electroluminescent (EL) display devices (e.g., organic EL display devices, inorganic EL display devices) can be cited. It goes without saying that the above description does not prevent the polarizing plate of the present invention from being applied to general image display devices.
[0035] The polarizer and the protective layer are described in detail below.
[0036] B. Polarizer
[0037] Any appropriate polarizer can be used as the polarizer. The polarizer can be typically produced using a laminate of two or more layers. The method for producing the polarizer will be described later in the section D as a method for producing a polarizing plate.
[0038] The thickness of the polarizer is preferably 1 μm to 8 μm, more preferably 1 μm to 7 μm, and even more preferably 2 μm to 5 μm.
[0039] The boric acid content of the polarizer is preferably 10% by weight or more, more preferably 13% by weight to 25% by weight. As long as the boric acid content of the polarizer is within such a range, the ease of curling adjustment during lamination can be maintained to be good through the synergistic effect with the iodine content described later, and the curling during heating can be well suppressed, while improving the appearance durability during heating. The boric acid content can be calculated, for example, by the neutralization method using the following formula as the amount of boric acid contained in the polarizer per unit weight.
[0040]
[0041] The iodine content of the polarizer is preferably 2% by weight or more, more preferably 2% to 10% by weight. As long as the iodine content of the polarizer is within this range, the ease of curling adjustment during lamination can be maintained well through the synergistic effect with the above-mentioned boric acid content, and the curling during heating can be well suppressed, while the durability of the appearance during heating can be improved. In this specification, "iodine content" refers to the amount of all iodine contained in the polarizer (PVA-based resin film). More specifically, iodine is present in the polarizer in the form of iodide ions (I - ), iodine molecules (I2), polyiodide ions (I3 - 、I5 - ) and other forms. The iodine content in this specification refers to the amount of iodine in all these forms. The iodine content can be calculated, for example, by the standard curve method of fluorescent X-ray analysis. It should be noted that the polyiodide ions exist in the polarizer in the form of a PVA-iodine complex. By forming such a complex, absorption dichroism can be exhibited in the wavelength range of visible light. Specifically, the complex of PVA and triiodide ion (PVA·I3 - ) has an absorption peak near 470nm, and the complex of PVA and pentaiodide ion (PVA·I5 - ) has an absorption peak near 600 nm. As a result, polyiodide ions can absorb light in a wide range of visible light depending on their form. On the other hand, iodide ions (I - ) has an absorption peak near 230nm and does not substantially participate in the absorption of visible light. Therefore, the polyiodide ions present in the form of a complex with PVA are mainly related to the absorption performance of the polarizer.
[0042] The polarizer preferably exhibits absorption dichroism at any wavelength between 380 nm and 780 nm. The single transmittance Ts of the polarizer is preferably 40% to 48%, more preferably 41% to 46%. The polarization degree P of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and further preferably 99.9% or more.
[0043] C. Protective layer
[0044] C-1.1st protective layer
[0045] As described above, the first protective layer is composed of a cured product of a coating film of an organic solvent solution of a thermoplastic acrylic resin (hereinafter referred to as an acrylic resin). The components of the first protective layer are described in detail below, and then the characteristics of the first protective layer are described.
[0046] C-1-1. Acrylic resin
[0047] The Tg of the acrylic resin (including a mixture of two or more acrylic resins and a mixture of an acrylic resin and other resins as described later) is as described in the description of the first protective layer in the above section A.
[0048] As the acrylic resin, any appropriate acrylic resin can be used as long as it has the Tg as described above. The acrylic resin typically contains an alkyl (meth)acrylate as a main component as a monomer unit (repeating unit). In this specification, "(meth)acrylic acid" refers to acrylic acid and / or methacrylic acid. As the alkyl (meth)acrylate constituting the main skeleton of the acrylic resin, there can be exemplified an alkyl (meth)acrylate having a carbon number of 1 to 18 in a linear or branched alkyl group. These can be used alone or in combination. Furthermore, any appropriate comonomer can be introduced into the acrylic resin by copolymerization. The repeating unit derived from the alkyl (meth)acrylate is typically represented by the following general formula (1):
[0049]
[0050] In the general formula (1), R 4 represents a hydrogen atom or a methyl group, R 5represents a hydrogen atom or an optionally substituted aliphatic or alicyclic hydrocarbon group having 1 to 6 carbon atoms. Examples of the substituent include halogen and hydroxyl groups. Specific examples of alkyl (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, benzyl (meth)acrylate, dicyclopentyloxyethyl (meth)acrylate, dicyclopentyl (meth)acrylate, chloromethyl (meth)acrylate, 2-chloroethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2,3,4,5,6-pentahydroxyhexyl (meth)acrylate, 2,3,4,5-tetrahydroxypentyl (meth)acrylate, methyl 2-(hydroxymethyl)acrylate, ethyl 2-(hydroxymethyl)acrylate, and methyl 2-(hydroxyethyl)acrylate. In the general formula (1), R 5 A hydrogen atom or a methyl group is preferred. Therefore, a particularly preferred alkyl (meth)acrylate is methyl acrylate or methyl methacrylate.
[0051] The acrylic resin may contain only a single (meth)acrylic acid alkyl ester unit, or may contain R 4 and R 5 Different types of alkyl (meth)acrylate units.
[0052] The content ratio of the (meth) alkyl acrylate unit in the acrylic resin is preferably 50 mol% to 98 mol%, more preferably 55 mol% to 98 mol%, further preferably 60 mol% to 98 mol%, particularly preferably 65 mol% to 98 mol%, and most preferably 70 mol% to 97 mol%. If the content ratio is less than 50 mol%, there is a risk that the effects (e.g., high heat resistance, high transparency) derived from the (meth) alkyl acrylate unit cannot be fully exerted. If the above-mentioned content ratio is greater than 98 mol%, the resin becomes brittle and easily cracked, and the high mechanical strength cannot be fully exerted, resulting in a risk of poor productivity.
[0053] The acrylic resin preferably has a repeating unit containing a ring structure. Examples of the repeating unit containing a ring structure include a lactone ring unit, a glutaric anhydride unit, a glutarimide unit, a maleic anhydride unit, and a maleimide (N-substituted maleimide) unit. The repeating unit of the acrylic resin may contain only one or more repeating units containing a ring structure.
[0054] The lactone ring unit is preferably represented by the following general formula (2):
[0055]
[0056] In the general formula (2), R 1 , R 2 and R 3 Each independently represents a hydrogen atom or an organic residue having 1 to 20 carbon atoms. It should be noted that the organic residue may also contain an oxygen atom. The acrylic resin may contain only a single lactone ring unit, or may contain R in the above general formula (2). 1 , R 2 and R 3 Different types of lactone ring units. The acrylic resin having a lactone ring unit is described in, for example, Japanese Patent Application Laid-Open No. 2008-181078, the contents of which are incorporated herein by reference.
[0057] The glutarimide unit is preferably represented by the following general formula (3):
[0058]
[0059] In the general formula (3), R 11 and R 12 Each independently represents hydrogen or an alkyl group having 1 to 8 carbon atoms, and R 13 represents an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an aryl group having 6 to 10 carbon atoms. 11 and R 12 are independently hydrogen or methyl and R 13 is hydrogen, methyl, butyl or cyclohexyl. 11 is methyl, R 12 is hydrogen, R 13 The acrylic resin may contain only a single glutarimide unit or may contain R in the above general formula (3). 11 , R 12 and R 13 A plurality of different glutarimide units. Acrylic resins having glutarimide units are described in, for example, Japanese Patent Publication No. 2006-309033, Japanese Patent Publication No. 2006-317560, Japanese Patent Publication No. 2006-328334, Japanese Patent Publication No. 2006-337491, Japanese Patent Publication No. 2006-337492, Japanese Patent Publication No. 2006-337493, and Japanese Patent Publication No. 2006-337569, and the descriptions of these publications are incorporated herein by reference. It should be noted that the glutaric anhydride unit is not limited to the glutaric anhydride unit in the general formula (3) replaced by R 13 Except that the substituted nitrogen atom is replaced by an oxygen atom, the above description on the glutarimide unit is applicable.
[0060] The structures of the maleic anhydride unit and the maleimide (N-substituted maleimide) unit can be identified by their names, and thus their specific descriptions are omitted.
[0061] The content ratio of the repeating unit containing a ring structure in the acrylic resin is preferably 1 mol% to 50 mol%, more preferably 10 mol% to 40 mol%, and further preferably 20 mol% to 30 mol%. When the content ratio is too low, Tg may be lower than 110° C., and the heat resistance, solvent resistance and surface hardness of the first protective layer obtained may become insufficient. When the content ratio is too high, the formability and transparency may be insufficient.
[0062] The acrylic resin may contain repeating units other than the (meth)acrylic acid alkyl ester unit and the repeating unit containing a ring structure. Examples of such repeating units include repeating units derived from vinyl monomers copolymerizable with the monomers constituting the above units (other vinyl monomer units). Examples of other vinyl monomers include acrylic acid, methacrylic acid, crotonic acid, 2-(hydroxymethyl)acrylic acid, 2-(hydroxyethyl)acrylic acid, acrylonitrile, methacrylonitrile, ethacrylonitrile, allyl glycidyl ether, maleic anhydride, itaconic anhydride, N-methylmaleimide, N-ethylmaleimide, N-cyclohexylmaleimide, aminoethyl acrylate, propylaminoethyl acrylate, dimethylaminoethyl methacrylate, ethylaminopropyl methacrylate, cyclohexylaminoethyl methacrylate, N-vinyldiethylamine, N-acetylvinylamine, allylamine, methylallylamine, N-methylallylamine, 2-isopropenyl-oxazoline, 2-vinyl-oxazoline, 2-acryloyl-oxazoline, N-phenylmaleimide, phenylaminoethyl methacrylate, styrene, α-methylstyrene, p-glycidylstyrene, p-aminostyrene, and 2-styryl-oxazoline. These may be used alone or in combination. The type, amount, combination, content ratio, etc. of other vinyl monomer units may be appropriately set depending on the purpose.
[0063] The weight average molecular weight of the acrylic resin is preferably 1,000 to 2,000,000, more preferably 5,000 to 1,000,000, further preferably 10,000 to 500,000, particularly preferably 50,000 to 500,000, and most preferably 60,000 to 150,000. The weight average molecular weight can be obtained, for example, by gel permeation chromatography (GPC system, manufactured by Tosoh Corporation) in terms of polystyrene. In addition, tetrahydrofuran can be used as a solvent.
[0064] The acrylic resin may be prepared by appropriately combining the above-mentioned monomer units and polymerizing them by any appropriate polymerization method. Two or more acrylic resins having different monomer units may be mixed.
[0065] In the embodiment of the present invention, acrylic resins and other resins can be used in combination. That is, the monomer components constituting the acrylic resin can be copolymerized with the monomer components constituting the other resins, and the copolymer can be used for the formation of the first protective layer described later; the mixture of the acrylic resin and other resins can also be used for the formation of the first protective layer. As other resins, thermoplastic resins such as styrene resins, polyethylene, polypropylene, polyamide, polyphenylene sulfide, polyetheretherketone, polyester, polysulfone, polyphenylene ether, polyacetal, polyimide, and polyetherimide can be cited. The type and blending amount of the resins used in combination can be appropriately set according to the purpose and the desired characteristics of the obtained film. For example, a styrene resin (preferably an acrylonitrile-styrene copolymer) can be used in combination as a phase difference controller.
[0066] When an acrylic resin and other resins are used in combination, the content of the acrylic resin in the mixture of the acrylic resin and other resins is preferably 50% by weight to 100% by weight, more preferably 60% by weight to 100% by weight, further preferably 70% by weight to 100% by weight, and particularly preferably 80% by weight to 100% by weight. When the content is less than 50% by weight, there is a risk that the high heat resistance and high transparency inherent in the acrylic resin may not be fully exhibited.
[0067] C-1-2. Composition and characteristics of the first protective layer
[0068] As described above, the first protective layer is composed of a cured product of a coating film of an organic solvent solution of an acrylic resin. As long as it is a cured product of such a coating film, the thickness can be made very thin compared to an extruded film. As described above, the thickness of the first protective layer is less than 10 μm, preferably less than 7 μm, more preferably less than 5 μm, and further preferably less than 3 μm. The lower limit of the thickness of the first protective layer may be, for example, 1 μm. In addition, although it is not clear in theory, the cured product of such a coating film has a smaller shrinkage during film forming than the cured product of a thermosetting (cured) resin or an active energy ray-curing resin (such as an ultraviolet curing resin) and does not contain residual monomers, etc. Therefore, it has the advantage of being able to suppress the deterioration of the film itself and suppressing the adverse effects on the polarizing plate (polarizer) caused by residual monomers, etc. Furthermore, since the hygroscopicity and moisture permeability are smaller than the cured product of an aqueous coating film such as an aqueous solution or an aqueous dispersion, it has the advantage of excellent humidification durability. As a result, a polarizing plate that can maintain optical properties even in a heated and humidified environment, that is, has excellent durability can be achieved.
[0069] The Tg of the first protective layer is as described in the above section A.
[0070] The iodine adsorption amount of the first protective layer is preferably 4.0 wt % or less, more preferably 3.0 wt % or less, further preferably 2.0 wt % or less, particularly preferably 1.0 wt % or less, and particularly preferably 0.5 wt % or less. The smaller the iodine adsorption amount, the more preferred it is, and its lower limit may be, for example, 0.1 wt %. As long as the iodine adsorption amount is within such a range, a polarizing plate with better durability can be obtained. The iodine adsorption amount can be measured by the method described in the examples described later.
[0071] The first protective layer is preferably substantially optically isotropic. In this specification, "substantially optically isotropic" means that the in-plane phase difference Re(550) is 0nm to 10nm, and the phase difference Rth(550) in the thickness direction is -20nm to +10nm. The in-plane phase difference Re(550) is more preferably 0nm to 5nm, further preferably 0nm to 3nm, and particularly preferably 0nm to 2nm. The phase difference Rth(550) in the thickness direction is more preferably -5nm to 5nm, further preferably -3nm to 3nm, and particularly preferably -2nm to 2nm. As long as the Re(550) and Rth(550) of the first protective layer are within such a range, when the polarizing plate containing the first protective layer is applied to an image display device, adverse effects on the display characteristics can be prevented. It should be noted that Re(550) is the in-plane phase difference of the film measured at 23°C with light of a wavelength of 550nm. Re(550) can be calculated by the formula: Re(550) = (nx-ny) × d. Rth(550) is the phase difference in the thickness direction of the film measured at 23°C with light of a wavelength of 550nm. Rth(550) can be calculated by the formula: Rth(550) = (nx-nz) × d. Here, nx is the refractive index in the direction where the refractive index in the plane reaches the maximum (i.e., the slow axis direction), ny is the refractive index in the direction orthogonal to the slow axis in the plane (i.e., the fast axis direction), nz is the refractive index in the thickness direction, and d is the thickness of the film (nm).
[0072] When the thickness of the first protective layer is 3 μm, the higher the transmittance at 380 nm, the more preferred. Specifically, the transmittance is preferably 85% or more, more preferably 88% or more, and further preferably 90% or more. As long as the transmittance is within this range, the desired transparency can be ensured. The transmittance can be measured, for example, by a method according to ASTM-D-1003.
[0073] The lower the haze of the first protective layer, the more preferred. Specifically, the haze is preferably 5% or less, more preferably 3% or less, further preferably 1.5% or less, and particularly preferably 1% or less. As long as the haze is 5% or less, the film can be given a good sense of transparency. Furthermore, even when used in the case of a polarizing plate on the visual recognition side of an image display device, the displayed content can be visually recognized well.
[0074] When the thickness of the first protective layer is 3 μm, the YI is preferably 1.27 or less, more preferably 1.25 or less, further preferably 1.23 or less, and particularly preferably 1.20 or less. When the YI is greater than 1.3, the optical transparency sometimes becomes insufficient. It should be noted that the YI can be obtained by the following formula using the tristimulus values (X, Y, Z) of the color obtained by measuring using a high-speed integrating sphere spectroscopic transmittance measuring machine (trade name DOT-3C: made by Murakami Color Technology Research Institute).
[0075] YI=[(1.28X-1.06Z) / Y]×100
[0076] When the thickness of the first protective layer is 3 μm, the b value (a measure of hue based on the Hunter color system) is preferably less than 1.5, and more preferably less than 1.0. When the b value is greater than 1.5, an undesirable hue may sometimes appear. It should be noted that the b value can be obtained, for example, as follows: a sample of the thin film constituting the first protective layer is cut into 3 cm squares, the hue is measured using a high-speed integrating sphere spectroscopic transmittance measuring machine (trade name DOT-3C: manufactured by Murakami Color Technology Research Institute), and the hue is evaluated based on the Hunter color system.
[0077] The first protective layer (cured product of the coating film) may contain any appropriate additives according to the purpose. Specific examples of additives include ultraviolet absorbers; leveling agents; antioxidants such as hindered phenols, phosphorus, and sulfur; stabilizers such as light stabilizers, weather stabilizers, and heat stabilizers; reinforcing materials such as glass fiber and carbon fiber; near-infrared absorbers; flame retardants such as tris(dibromopropyl) phosphate, triallyl phosphate, and antimony oxide; antistatic agents such as anionic, cationic, and nonionic surfactants; colorants such as inorganic pigments, organic pigments, and dyes; organic fillers or inorganic fillers; resin modifiers; organic fillers or inorganic fillers; plasticizers; lubricants; antistatic agents; flame retardants, etc. The additives may be added during the polymerization of the acrylic resin, or added to the solution during the film formation. The type, quantity, combination, and addition amount of the additives may be appropriately set according to the purpose.
[0078] An easy-adhesion layer may be formed on the polarizer side of the first protective layer. The easy-adhesion layer includes, for example, water-based polyurethane and an oxazoline-based crosslinking agent. By forming such an easy-adhesion layer, the adhesion between the first protective layer and the polarizer can be improved.
[0079] C-2. Second protective layer
[0080] The second protective layer is made of resin film as mentioned above. For the specific example of the material as the main component of this film, cellulose resins such as triacetylcellulose (TAC), polyester resins such as polyethylene terephthalate (PET), polyvinyl alcohol resins, polycarbonate resins, polyamide resins, polyimide resins, polyethersulfone resins, polysulfone resins, polystyrene resins, cycloolefin resins such as polynorbornene, polyolefin resins, (methyl) acrylic resins and acetate resins and other transparent resins can be enumerated. In addition, thermosetting resins or ultraviolet curing resins such as (methyl) acrylic acid, carbamate, (methyl) acrylic acid carbamate, epoxy, silicone can also be enumerated. Other glassy polymers such as siloxane polymers can also be enumerated. In addition, the polymer film recorded in Japanese Patent Publication No. 2001-343529 (WO01 / 37007) can also be used. As the material of the film, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group in the side chain and a thermoplastic resin having a substituted or unsubstituted phenyl group and a nitrile group in the side chain can be used, for example, a resin composition containing an alternating copolymer formed by isobutylene and N-methylmaleimide and an acrylonitrile-styrene copolymer can be mentioned. The polymer film can be, for example, an extrusion molding of the above resin composition.
[0081] When the polarizing plate of the present invention is arranged on the visual recognition side of the image display device and the second protective layer 30 is arranged on the side (visual recognition side) opposite to the display unit of the image display device, the second protective layer 30 may be subjected to surface treatments such as hard coating, anti-reflection, anti-adhesion, and anti-glare as needed. Furthermore, / or, the second protective layer 30 may also be subjected to treatments for improving visual recognition when visually recognized through polarized sunglasses as needed (representatively, imparting (elliptical) polarization function and imparting ultra-high phase difference). By implementing such treatments, excellent visual recognition can be achieved even when visually recognizing the displayed image through polarized lenses such as polarized sunglasses. Therefore, the polarizing plate may also be suitable for use in image display devices that can be used outdoors.
[0082] The thickness of the second protective layer is preferably 10 μm to 50 μm, and more preferably 10 μm to 30 μm. When the surface treatment is performed, the thickness of the outer protective layer is the thickness including the thickness of the surface treatment layer.
[0083] D. Manufacturing method of polarizing plate
[0084] D-1. Method for manufacturing polarizer
[0085] The method for manufacturing the polarizer described in item B above includes: forming a polyvinyl alcohol resin layer (PVA resin layer) containing a halide and a polyvinyl alcohol resin (PVA resin) on one side of a long thermoplastic resin substrate to form a laminate; and sequentially subjecting the laminate to an air auxiliary stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment, wherein the drying shrinkage treatment heats the laminate while conveying it in the long side direction, thereby shrinking it by more than 2% in the width direction. The content of the halide in the PVA resin layer is preferably 5 to 20 parts by weight relative to 100 parts by weight of the PVA resin. The drying shrinkage treatment is preferably carried out using a heating roller, and the temperature of the heating roller is preferably 60°C to 120°C. According to such a manufacturing method, a polarizer as described above can be obtained. In particular, by making a laminate including a PVA-based resin layer containing a halide, setting the stretching of the above-mentioned laminate to a multi-stage stretching including auxiliary stretching in the air and stretching in water, and heating the stretched laminate using a heating roller, a polarizer having excellent optical properties (representatively, monomer transmittance and polarization degree) and suppressed optical property unevenness can be obtained. Specifically, by using a heating roller in the drying and shrinking treatment process, the laminate can be uniformly shrunk as a whole while conveying the laminate. As a result, not only the optical properties of the obtained polarizer can be improved, but also polarizers with excellent optical properties can be stably produced, and the unevenness of the optical properties of the polarizer (especially monomer transmittance) can be suppressed. Below, halides and drying shrinkage treatment are described. For details of the manufacturing method other than these, for example, it is recorded in Japanese Patent Gazette No. 2012-73580. The entire record of the gazette is cited in this specification as a reference.
[0086] D-1-1. Halides
[0087] The PVA resin layer containing a halide and a PVA resin can be formed by applying a coating solution containing a halide and a PVA resin on a thermoplastic resin substrate and drying the coating film. The coating solution is typically a solution in which the halide and the PVA resin are dissolved in a solvent. As solvents, for example, water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, various glycols, polyols such as trimethylolpropane, amines such as ethylenediamine and diethylenetriamine can be cited. These can be used alone or in combination of two or more. Among these, water is preferred. The PVA resin concentration of the solution is preferably 3 to 20 parts by weight relative to 100 parts by weight of the solvent. As long as the resin concentration is such, a uniform coating film that is closely attached to the thermoplastic resin substrate can be formed.
[0088] As the halide, any appropriate halide can be used. Examples thereof include iodide and sodium chloride. As the iodide, examples thereof include potassium iodide, sodium iodide and lithium iodide. Among these, potassium iodide is preferred.
[0089] The amount of the halide in the coating solution is preferably 5 to 20 parts by weight, more preferably 10 to 15 parts by weight, based on 100 parts by weight of the PVA-based resin. If the amount of the halide is too large, the halide may bleed out and the resulting polarizer may become cloudy.
[0090] Generally speaking, after the PVA resin layer is stretched, the orientation of the polyvinyl alcohol molecules in the PVA resin becomes higher. However, if the stretched PVA resin layer is immersed in a water-containing liquid, the orientation of the polyvinyl alcohol molecules is sometimes disordered and the orientation is reduced. In particular, when the laminate of the thermoplastic resin substrate and the PVA resin layer is stretched in boric acid water, in order to stabilize the stretching of the thermoplastic resin substrate, when the laminate is stretched in boric acid water at a relatively high temperature, the tendency for the orientation to decrease is significant. For example, the stretching of the PVA film itself in boric acid water is usually carried out at 60°C. In contrast, the stretching of the laminate of A-PET (thermoplastic resin substrate) and the PVA resin layer is carried out at a relatively high temperature of about 70°C. At this time, the orientation of the PVA at the initial stage of stretching will decrease in the stage before it rises by stretching in water. In this regard, by preparing a laminate of a PVA-based resin layer containing a halide and a thermoplastic resin substrate, and performing high-temperature stretching (auxiliary stretching) in air before stretching the laminate in boric acid water, the crystallization of the PVA-based resin in the PVA-based resin layer of the laminate after auxiliary stretching can be promoted. As a result, when the PVA-based resin layer is immersed in a liquid, the orientation disorder and the reduction of the orientation of the polyvinyl alcohol molecules can be suppressed more than when the PVA-based resin layer does not contain a halide. As a result, the optical properties of the polarizer obtained by the treatment process of immersing the laminate in a liquid such as dyeing treatment and underwater stretching treatment can be improved.
[0091] D-1-2. Drying shrinkage treatment
[0092] The drying shrinkage treatment can be carried out by heating the region as a whole, or by heating the conveying roller (using the so-called heating roller) (heating roller drying method). Preferably, both are used. By using a heating roller to dry it, the heating curling of the laminate can be effectively suppressed, and a polarizer with excellent appearance can be manufactured. Specifically, by drying the laminate along the heating roller, the crystallization of the above-mentioned thermoplastic resin substrate can be effectively promoted to increase the degree of crystallization, even at a lower drying temperature, the degree of crystallization of the thermoplastic resin substrate can be well increased. As a result, the rigidity of the thermoplastic resin substrate increases and becomes a state that can withstand the shrinkage of the PVA-based resin layer caused by drying, so that curling is suppressed. In addition, by using a heating roller, the laminate can be dried while maintaining a flat state, so that not only the generation of curling can be suppressed, but also the generation of wrinkles can be suppressed. At this time, the laminate shrinks in the width direction by the drying shrinkage treatment, so that the optical properties can be improved. This is because the orientation of PVA and PVA / iodine complex can be effectively improved. The shrinkage rate of the laminate in the width direction based on the drying shrinkage treatment is preferably 2% to 10%, more preferably 2% to 8%, and particularly preferably 4% to 6%. By using a heated roller, the laminate can be continuously shrunk in the width direction while being conveyed, and high productivity can be achieved.
[0093] Figure 2 Schematic diagram showing an example of drying shrinkage treatment. In the drying shrinkage treatment, the laminate 200 is dried while being transported by using conveying rollers R1 to R6 and guide rollers G1 to G4 heated to a predetermined temperature. In the example shown in the figure, the conveying rollers R1 to R6 are arranged so as to alternately and continuously heat the surface of the PVA resin layer and the surface of the thermoplastic resin substrate, but, for example, the conveying rollers R1 to R6 may be arranged so as to continuously heat only one surface of the laminate 200 (for example, the surface of the thermoplastic resin substrate).
[0094] The drying conditions can be controlled by adjusting the heating temperature of the conveying roller (the temperature of the heating roller), the number of heating rollers, the contact time with the heating roller, etc. The temperature of the heating roller is preferably 60°C to 120°C, more preferably 65°C to 100°C, and particularly preferably 70°C to 80°C. An optical laminate with excellent durability can be produced while the degree of crystallization of the thermoplastic resin can be increased well and curling can be suppressed well. It should be noted that the temperature of the heating roller can be measured using a contact thermometer. In the example shown in the figure, 6 conveying rollers are provided, but there is no particular limitation as long as there are multiple conveying rollers. Conveying rollers are usually provided in 2 to 40 numbers, preferably 4 to 30 numbers. The contact time (total contact time) between the laminate and the heating roller is preferably 1 second to 300 seconds, more preferably 1 to 20 seconds, and further preferably 1 to 10 seconds.
[0095] The heating roller can be set in a heating furnace (such as an oven) or in a general manufacturing line (under room temperature environment). It is preferably set in a heating furnace equipped with air supply means. By combining the drying based on the heating roller and the hot air drying, the rapid temperature change between the heating rollers can be suppressed, and the shrinkage in the width direction can be easily controlled. The temperature of the hot air drying is preferably 30°C to 100°C. In addition, the hot air drying time is preferably 1 second to 300 seconds. The wind speed of the hot air is preferably about 10m / s to 30m / s. It should be noted that the wind speed is the wind speed in the heating furnace, which can be measured using a mini fan-type digital anemometer.
[0096] It is preferred that a washing treatment be performed after the underwater stretching treatment and before the drying shrinkage treatment. The above-mentioned washing treatment can be typically performed by immersing the PVA-based resin layer in an aqueous potassium iodide solution.
[0097] Thereby, a laminate of thermoplastic resin substrate / polarizer can be obtained.
[0098] D-2. Method for manufacturing polarizing plate
[0099] A resin film constituting the second protective layer is attached to the surface of the polarizer of the laminate obtained in the above-mentioned item D-1. Next, the thermoplastic resin substrate is peeled off, and an organic solvent solution of an acrylic resin is applied to the peeled surface to form a coating film, and the coating film is cured to form the first protective layer. Thus, a polarizing plate having a structure of the first protective layer (cured product of the coating film) / polarizer / second protective layer (resin film) can be obtained.
[0100] The acrylic resin is as described in the above section C-1-1.
[0101] As the organic solvent, any appropriate organic solvent that can dissolve or uniformly disperse the acrylic resin can be used. Specific examples of the organic solvent include ethyl acetate, toluene, methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), cyclopentanone, and cyclohexanone.
[0102] The acrylic resin concentration of the solution is preferably 3 to 20 parts by weight relative to 100 parts by weight of the solvent. With such a resin concentration, a uniform coating film that is closely attached to the polarizer can be formed.
[0103] The solution can be applied to any appropriate substrate, and can also be applied to a polarizer. When the solution is applied to the substrate, the cured product of the coating film formed on the substrate is transferred to the polarizer. When the solution is applied to the polarizer, the first protective layer is directly formed on the polarizer by drying (curing) the coating film. Preferably, the solution is applied to the polarizer to form the first protective layer directly on the polarizer. As long as it is such a structure, the adhesive layer or adhesive layer required for transfer can be omitted, so the polarizing plate can be made thinner. As a method for applying the solution, any appropriate method can be adopted. As specific examples, roller coating, spin coating, wire rod coating, dip coating, die coating, curtain coating, spray coating, and blade coating (comma coating, etc.) can be cited.
[0104] The first protective layer can be formed by drying (curing) the coating film of the solution. The drying temperature is preferably 100°C or less, more preferably 50°C to 70°C. As long as the drying temperature is within this range, adverse effects on the polarizer can be prevented. The drying time can vary depending on the drying temperature. The drying time can be, for example, 1 minute to 10 minutes.
[0105] As above, a polarizing plate having a structure of a first protective layer (cured product of the coating film) / polarizer / second protective layer (resin film) can be obtained. Alternatively, the thermoplastic resin substrate can be directly used as the second protective layer. At this time, an organic solvent solution of an acrylic resin is applied to the surface of the polarizer of the laminate of the thermoplastic resin substrate / polarizer to form a coating film, and the coating film is cured to form the first protective layer. As a result, a polarizing plate having a structure of a first protective layer (cured product of the coating film) / polarizer / second protective layer (thermoplastic resin substrate) can be obtained.
[0106] Example
[0107] The present invention is specifically described below with reference to examples, but the present invention is not limited to these examples. The measuring methods of various properties are as follows. It should be noted that, unless otherwise specified, the "parts" and "%" in the examples are based on weight.
[0108] (1) Glass transition temperature Tg
[0109] The solution obtained by dissolving the material constituting the first protective layer used in the examples and comparative examples in a prescribed solvent was applied to the substrate (PET film) using an applicator and dried at 60°C to form a coating film (thickness 40 μm). The obtained coating film was peeled off from the substrate and cut into strips as a measurement sample. The measurement sample was subjected to DMA measurement to measure Tg. The measurement device and measurement conditions are as follows.
[0110] (Measurement device)
[0111] Made by SII NanoTechnology Inc., "DMS6100"
[0112] (Measurement conditions)
[0113] ·Measurement temperature range: -80℃~150℃
[0114] Heating and cooling speed: 2℃ / min
[0115] ·Test sample width: 10mm
[0116] Distance between fixtures: 20mm
[0117] ·Measurement frequency: 1Hz
[0118] Strain amplitude: 10μm
[0119] ·Measurement atmosphere: N2 (250mL / min)
[0120] (2) Iodine adsorption
[0121] A solution obtained by dissolving the material constituting the first protective layer used in the examples and comparative examples in a predetermined solvent was applied to a substrate (PET film) using an applicator and dried at 60° C. to form a coating film (thickness 40 μm). The obtained coating film was peeled off from the substrate and cut into 1 cm×1 cm (1 cm 2 ) as the test sample. The test sample is provided to the combustion IC method to quantitatively analyze the iodine content in the sample. The details are as follows. Take the test sample and weigh it and put it into a headspace vial (20mL capacity). Next, a vial (2mL capacity) containing 1mL of iodine solution (iodine concentration 1 weight%, potassium iodide concentration 7 weight%) is placed in the headspace vial and covered tightly. Afterwards, the headspace vial is heated at 65°C in a dryer for 6 hours, the heated sample is taken and placed in a ceramic dish and burned using an automatic combustion device, so that the absorption liquid captures the generated gas, and then a quantitative analysis is performed to obtain the weight % of the adsorbed iodine. It should be noted that the device used is as follows.
[0122] ·Automatic sample combustion device: Mitsubishi Chemical Analytech, "AQF-2100H"
[0123] IC (anion): manufactured by Thermo Fisher Scientific, “ICS-3000”
[0124] (3) Decolorization
[0125] A test piece (50 mm × 50 mm) was cut out from the polarizing plate obtained in the embodiment and the comparative example, and the test piece formed two sides which were respectively opposite to the direction perpendicular to the absorption axis direction of the polarizer and the absorption axis direction. The test piece was bonded to the alkali-free glass plate with an adhesive in such a way that the first protective layer became the inner side to prepare a test sample, and the test sample was placed in an oven at 85°C and 85% RH for 48 hours for heating and humidification, and the discoloration state of the humidified polarizing plate when configured to form a cross prism with the standard polarizing plate was visually observed, and evaluated according to the following criteria.
[0126] No problem: no discoloration observed
[0127] Partial discoloration: Discoloration is observed at the end
[0128] Total discoloration: The polarizing plate is obviously discolored as a whole
[0129] (4) Single-body transmittance and polarization
[0130] A test piece (50 mm × 50 mm) was cut out from the polarizing plate obtained from the embodiment and the comparative example, and the test piece formed two sides opposite to the direction perpendicular to the absorption axis direction of the polarizer and the absorption axis direction, respectively. The test piece was bonded to an alkali-free glass plate with an adhesive with the protective layer as the outer side to prepare a test sample. The single transmittance (Ts), parallel transmittance (Tp) and orthogonal transmittance (Tc) of the test sample were measured using an ultraviolet visible spectrophotometer (manufactured by JASCO Corporation, product name "V7100"), and the polarization degree (P) was calculated using the following formula. At this time, the measuring light was incident from the protective layer side.
[0131] Polarization degree (P) (%) = {(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100
[0132] It should be noted that the above Ts, Tp and Tc are Y values obtained by measuring with a 2-degree field of view (light source C) according to JIS Z 8701 and correcting the visual sensitivity. In addition, Ts and P are substantially characteristics of the polarizer.
[0133] Then, the polarizing plate was placed in an oven at 85°C and 85% RH for 48 hours for heating and humidification (heating test). Then, the single transmittance Ts0 before the heating test and the single transmittance Ts after the heating test were calculated. 48 , the single transmittance change ΔTs is calculated using the following formula.
[0134] ΔTs(%)=Ts 48 -Ts0
[0135] Similarly, the polarization degree P0 before the heating test and the polarization degree P0 after the heating test are 48, use the following formula to calculate the change in polarization degree ΔP.
[0136] ΔP(%)=P 48 -P0
[0137] In addition, the heating test was carried out by preparing a test sample in the same manner as in the above-mentioned decolorization.
[0138] <Example 1>
[0139] 1. Preparation of polarizer / resin substrate laminate
[0140] As the resin substrate, a long amorphous polyethylene terephthalate copolymer film (thickness: 100 μm) having a water absorption rate of 0.75% and a Tg of about 75° C. was used. One surface of the resin substrate was subjected to a corona treatment.
[0141] To 100 parts by weight of a PVA-based resin prepared by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER Z410") in a ratio of 9:1, 13 parts by weight of potassium iodide was added to prepare a PVA aqueous solution (coating solution).
[0142] The PVA aqueous solution was applied to the corona-treated surface of the resin substrate and dried at 60° C., thereby forming a PVA-based resin layer having a thickness of 13 μm, thereby producing a laminate.
[0143] The obtained laminate was subjected to free-end uniaxial stretching to 2.4 times in the longitudinal direction (longitudinal direction) between rolls having different peripheral speeds in an oven at 130° C. (in-air auxiliary stretching treatment).
[0144] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution prepared by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilization treatment).
[0145] Next, the polarizer was immersed in a dyeing bath (an iodine aqueous solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 relative to 100 parts by weight of water) at a temperature of 30° C. for 60 seconds while adjusting the concentration so that the single body transmittance (Ts) of the final polarizer became 41.5%±0.1% (dyeing treatment).
[0146] Next, the film was immersed in a crosslinking bath (boric acid aqueous solution prepared by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment).
[0147] Then, while the laminate was immersed in a boric acid aqueous solution (boric acid concentration: 4.0 wt%) at a liquid temperature of 70°C, it was uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls having different peripheral speeds so that the total stretching ratio became 5.5 times (underwater stretching treatment).
[0148] Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution prepared by mixing 4 parts by weight of potassium iodide with respect to 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment).
[0149] Thereafter, the laminate was dried in an oven maintained at 90° C. while being brought into contact with a SUS heating roll having a surface temperature maintained at 75° C. for about 2 seconds (drying shrinkage treatment). The shrinkage rate in the width direction of the laminate due to the drying shrinkage treatment was 5.2%.
[0150] As described above, a polarizer with a thickness of 5 μm was formed on the resin substrate to produce a polarizer / resin substrate laminate. The single transmittance (initial single transmittance) Ts0 of the polarizer was 41.5, and the polarization degree (initial polarization degree) P0 was 99.996%.
[0151] 2. Production of polarizing plate
[0152] A cycloolefin film (ZT-12, 23 μm thick, manufactured by Zeon Co., Ltd., Japan) is bonded to the surface of the polarizer obtained above as a film constituting the second protective layer by means of an ultraviolet curing adhesive. Specifically, the curing adhesive is applied in a manner with a total thickness of 1.0 μm and bonded using a rolling mill. Thereafter, UV light is irradiated from the film side to cure the adhesive. Next, the resin substrate is peeled off to obtain a polarizing plate having a second protective layer (ZT-12) / polarizer configuration.
[0153] 20 parts of an acrylic resin (lactone ring unit 30 mol%) which is polymethyl methacrylate having a lactone ring unit are dissolved in 80 parts of methyl ethyl ketone to obtain an acrylic resin solution (20%). The acrylic resin solution is applied to the surface of the polarizer of the polarizing plate obtained above using a wire rod, and the coated film is dried at 60°C for 5 minutes to form a first protective layer in the form of a cured product of the coating film. The first protective layer has a thickness of 3 μm, a Tg of 119°C, and an iodine adsorption amount of 0.25 wt%. By operating as above, a polarizing plate having a structure of a first protective layer (cured product of the coating film) / polarizer / second protective layer (ZT-12) is obtained. The obtained polarizing plate is provided for the evaluation of (3) and (4) above. Furthermore, the protective layer is visually observed to see if there is any shrinkage after formation. The results are shown in Table 1.
[0154] <Example 2>
[0155] The first protective layer was formed in the same manner as in Example 1 except that an acrylic resin (maleic anhydride unit 7 mol%) of polymethyl methacrylate having a maleic anhydride unit was used instead of an acrylic resin of polymethyl methacrylate having a lactone ring unit. The first protective layer had a thickness of 3 μm and a Tg of 115° C. A polarizing plate was prepared in the same manner as in Example 1 except that the first protective layer was used. The obtained polarizing plate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0156] <Example 3>
[0157] The first protective layer was formed in the same manner as in Example 1, except that an acrylic resin of 100% polymethyl methacrylate (manufactured by Kusumoto Chemicals Co., Ltd., product name "B-728") was used instead of an acrylic resin of polymethyl methacrylate having a lactone ring unit. The first protective layer had a thickness of 3 μm, a Tg of 116° C., and an iodine adsorption amount of 0.34% by weight. A polarizing plate was prepared in the same manner as in Example 1, except that the first protective layer was used. The obtained polarizing plate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0158] <Example 4>
[0159] The first protective layer was formed in the same manner as in Example 1 except that an acrylic resin of polymethyl methacrylate having a glutarimide ring unit (glutarimide ring unit 4 mol%) was used instead of an acrylic resin of polymethyl methacrylate having a lactone ring unit. The first protective layer had a thickness of 3 μm, a Tg of 103° C., and an iodine adsorption amount of 2.3 wt %. A polarizing plate was prepared in the same manner as in Example 1 except that the first protective layer was used. The obtained polarizing plate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0160] <Example 5>
[0161] The first protective layer was formed in the same manner as in Example 1 except that a different acrylic resin of polymethyl methacrylate having a lactone ring unit (lactone ring unit 20 mol%) was used. The first protective layer had a thickness of 3 μm, a Tg of 104° C., and an iodine adsorption amount of 2.8 wt %. A polarizing plate was prepared in the same manner as in Example 1 except that the first protective layer was used. The obtained polarizing plate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0162] <Example 6>
[0163] The first protective layer was formed in the same manner as in Example 1, except that an acrylic resin of a copolymer of methyl methacrylate / butyl methacrylate (molar ratio 80 / 20) was used instead of an acrylic resin of polymethyl methacrylate having a lactone ring unit. The first protective layer had a thickness of 3 μm, a Tg of 95° C., and an iodine adsorption amount of 3.8 wt %. A polarizing plate was prepared in the same manner as in Example 1, except that the first protective layer was used. The obtained polarizing plate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0164] <Comparative Example 1>
[0165] The first protective layer was formed in the same manner as in Example 1, except that an acrylic resin (manufactured by Kusumoto Chemicals Co., Ltd., product name "B-722") which is a copolymer of methyl methacrylate / ethyl acrylate (molar ratio 55 / 45) was used instead of an acrylic resin of polymethyl methacrylate having a lactone ring unit. The first protective layer had a thickness of 3 μm, a Tg of 39°C, and an iodine adsorption amount of 1.7% by weight. A polarizing plate was prepared in the same manner as in Example 1, except that the first protective layer was used. The obtained polarizing plate was subjected to a decolorization evaluation, and the result was poor ("complete decolorization"), so the monomer transmittance and polarization degree were not evaluated. The results are shown in Table 1.
[0166] <Comparative Example 2>
[0167] The first protective layer was formed in the same manner as in Example 1, except that an acrylic resin (manufactured by Kusumoto Chemicals Co., Ltd., product name "B-734") which is a copolymer of methyl methacrylate / butyl methacrylate (molar ratio 35 / 65) was used instead of an acrylic resin of polymethyl methacrylate having a lactone ring unit. The first protective layer had a thickness of 3 μm, a Tg of 71°C, and an iodine adsorption amount of 12% by weight. A polarizing plate was prepared in the same manner as in Example 1, except that the first protective layer was used. The obtained polarizing plate was subjected to a decolorization evaluation, and the result was poor ("complete decolorization"), so the monomer transmittance and polarization degree were not evaluated. The results are shown in Table 1.
[0168] <Comparative Example 3>
[0169] The first protective layer (cured product) was formed in the same manner as in Example 1 except that an ultraviolet curable acrylic resin (manufactured by Kyoeisha Chemical, product name "LIGHT ACRYLATE HPP-A", neopentyl glycol hydroxypivalate acrylic acid adduct) was used. Specifically, a composition prepared by mixing 97 wt % of the acrylic resin and 3 wt % of a photopolymerization initiator (IRGACURE 907, manufactured by BASF) was applied to the polarizer and illuminated with a high pressure mercury lamp in a nitrogen atmosphere at a cumulative light intensity of 300 mJ / cm 2The cured layer (first protective layer) was formed by irradiating with ultraviolet rays. The first protective layer had a thickness of 3 μm, a Tg of 83° C., and an iodine adsorption amount of 6.6% by weight. A polarizing plate was prepared in the same manner as in Example 1 except that the first protective layer was used. The obtained polarizing plate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0170] <Comparative Example 4>
[0171] The first protective layer (cured product) was formed in the same manner as in Example 1 except that an ultraviolet curable acrylic resin (manufactured by Toagosei Co., Ltd., product name "ARONIX M-402" and dipentaerythritol penta- and hexa-acrylates (penta-acrylate is 30% to 40%) was used. The method for forming the first protective layer was the same as in Comparative Example 3. The thickness of the first protective layer was 3 μm. A polarizing plate was produced in the same manner as in Example 1 except that the first protective layer was used. The obtained polarizing plate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0172] <Comparative Example 5>
[0173] The first protective layer (cured product) was formed in the same manner as in Example 1 except that an ultraviolet curable epoxy resin (manufactured by DAICEL, product name "CELLOXIDE 2021P") was used. Specifically, a composition prepared by mixing 95 wt % of the epoxy resin and 5 wt % of a photopolymerization initiator (CPI-100P, manufactured by San-Apro) was applied to the polarizer and illuminated with a high pressure mercury lamp in an air atmosphere at a cumulative light intensity of 500 mJ / cm 2 The cured layer (first protective layer) was formed by irradiating with ultraviolet rays. The first protective layer had a thickness of 3 μm, a Tg of 95° C., and an iodine adsorption amount of 9 wt %. A polarizing plate was prepared in the same manner as in Example 1 except that the first protective layer was used. The obtained polarizing plate was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0174] <Comparative Example 6>
[0175] The first protective layer (cured product of the coating film) was formed in the same manner as in Example 1 except that a water-based polyester resin (manufactured by Nippon Synthetic Chemical Co., Ltd., product name "POLYESTER WR905") was used. The thickness of the first protective layer was 3 μm, and the iodine adsorption amount was 12% by weight. A polarizing plate was prepared in the same manner as in Example 1 except that the first protective layer was used. The obtained polarizing plate was subjected to a decolorization evaluation, and the result was poor ("complete decolorization"), so the monomer transmittance and polarization degree were not evaluated. The results are shown in Table 1.
[0176] <Comparative Example 7>
[0177] Except for using an aqueous polyurethane resin (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name “SUPERFLEX SF210”), the same operations as in Example 1 were carried out to form the first protective layer (the cured product of the coating film). The thickness of the first protective layer was 3 μm, the Tg was 107 °C, and the iodine adsorption amount was 19% by weight. Except for using this first protective layer, the same operations as in Example 1 were carried out to produce a polarizing plate. The obtained polarizing plate was subjected to a decolorization evaluation, and the result was poor (“completely decolorized”), so the evaluation of the monomer transmittance and the degree of polarization was not carried out. The results are shown in Table 1.
[0178] <Comparative Example 8>
[0179] Except for using an aqueous polyurethane resin (manufactured by Unitika Ltd., product name “ARROW BASE SE1200”), the same operations as in Example 1 were carried out to form the first protective layer (the cured product of the coating film). The thickness of the first protective layer was 3 μm, and the iodine adsorption amount was 15% by weight. Except for using this first protective layer, the same operations as in Example 1 were carried out to produce a polarizing plate. The obtained polarizing plate was subjected to a decolorization evaluation, and the result was poor (“completely decolorized”), so the evaluation of the monomer transmittance and the degree of polarization was not carried out. The results are shown in Table 1.
[0180] [Table 1]
[0181]
[0182] *(sol) indicates an organic solvent system, and (water) indicates an aqueous system
[0183] <Evaluation>
[0184] As can be seen from Table 1, the polarizing plate of the example of the present invention is a polarizing plate that, although very thin, can suppress the deterioration of optical properties in a heated and humid environment, has excellent durability, and does not shrink after the formation of the protective layer and can withstand practical applications.
[0185] Industrial Applicability
[0186] The polarizing plate of the present invention is suitable for use in an image display device. Examples of the image display device include portable devices such as a portable information terminal (PDA), a smart phone, a mobile phone, a watch, a digital camera, and a portable game machine; OA devices such as a computer monitor, a notebook computer, and a copying machine; household electrical appliances such as a video camera, a television, and a microwave oven; in-vehicle devices such as a rear monitor, a monitor for a car navigation system, and a car audio; display devices such as a digital signage and a display for commercial store information; security devices such as a surveillance monitor; and nursing / medical devices such as a nursing monitor and a medical monitor.
[0187] Explanation of Reference Numerals
[0188] 10 Polarizing member
[0189] 201st protection layer
[0190] 30Second protection layer
[0191] 100 polarizing plates
Claims
1. A polarizing plate comprising a polarizer containing iodine and a polyvinyl alcohol-based resin, a first protective layer disposed on one side of the polarizer, and a second protective layer disposed on the other side of the polarizer; The glass transition temperature of the first protective layer is above 95°C; The iodine adsorption amount of the first protective layer is less than 4.0 wt %; The second protective layer is composed of a resin film; The thickness of the first protective layer is less than 5 μm; The first protective layer is formed directly on the polarizer, and is composed of a cured product of a coating film formed by directly applying an organic solvent solution of a thermoplastic acrylic resin to the surface of the polarizer.
2. The polarizing plate according to claim 1, wherein The thermoplastic acrylic resin has at least one selected from the group consisting of a lactone ring unit, a glutaric anhydride unit, a glutarimide unit, a maleic anhydride unit, and a maleimide unit.
3. The polarizing plate according to claim 1 or 2, wherein: The first protective layer has an in-plane phase difference Re(550) of 0 nm to 10 nm, and a thickness direction phase difference Rth(550) of -20 nm to +10 nm.
4. The polarizing plate according to any one of claims 1 to 3, wherein The first protective layer is arranged on a display unit side of the image display device, and the second protective layer is arranged on an opposite side to the display unit. The polarizing plate according to claim 4 , which is disposed on a viewing side of an image display device. 6 . A polarizing plate roll, wherein the polarizing plate according to claim 1 is wound into a roll.
Citation Information
Patent Citations
Polarizer protective film, polarizing plate and image display
CN101253431A
Polarizing plate and liquid crystal display device
CN105729963A
Polarizer, image display device and method for producing said image display device
CN110520770A
Thermoplastic resin composition, and resin molded article and polarizer protecting film using it, as well as manufacturing method of resin molded article
JP2009052021A
Thermoplastic resin composition and optical film using the same
JP2016147949A